42.5k views
4 votes
Find the solution set. (x+9) (x+9) = 0

1 Answer

4 votes

Answer:

The solution set is
x=-9

Explanation:

we have


(x+9)(x+9)=0

we know that


(x+9)(x+9)=x^(2)+18x+81

so


x^(2)+18x+81=0

The formula to solve a quadratic equation of the form
ax^(2) +bx+c=0 is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


x^(2)+18x+81=0

so


a=1\\b=18\\c=81

substitute in the formula


x=\frac{-18(+/-)\sqrt{18^(2)-4(1)(81)}} {2(1)}


x=\frac{-18(+/-)√(0)} {2}

The radicand is equal to zero, therefore, the solution has only one real solution


x=\frac{-18} {2}=-9

User CYee
by
6.6k points